2017
DOI: 10.1186/s12889-017-4149-3
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effects of a campaign supporting use of a health symbol on food sales and shopping behaviour of consumers

Abstract: BackgroundSince 2009, the green Keyhole symbol has been a joint Nordic initiative for signalling healthfulness of specific food products. In 2014, the Danish Ministry of Food, Agriculture and Fisheries carried out a campaign aimed mainly at men over 35 with a low level of education, encouraging them to use the Keyhole in their shopping process. The objective of the study is to evaluate the campaign by measuring its effect on consumer behaviour in the store.MethodsThe impact of the Keyhole campaign was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Although nutrition-related messages had a positive effect on visual attention to the warnings and the healthfulness of the snack choices, it should be acknowledged that the study evaluated only their immediate effect. Although signages and promotional materials in-store may contribute to raise awareness of the existence of FOP nutrition labelling on food packages and promote their use, previous studies have shown that actual use of such materials is limited (12) . Considering that use of the FOP nutrition labelling is strongly dependent on the salience of the health motive at the point of purchase, multimedia campaigns aimed at increasing health motivation may be more efficient than promotional materials at the point of purchase (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Although nutrition-related messages had a positive effect on visual attention to the warnings and the healthfulness of the snack choices, it should be acknowledged that the study evaluated only their immediate effect. Although signages and promotional materials in-store may contribute to raise awareness of the existence of FOP nutrition labelling on food packages and promote their use, previous studies have shown that actual use of such materials is limited (12) . Considering that use of the FOP nutrition labelling is strongly dependent on the salience of the health motive at the point of purchase, multimedia campaigns aimed at increasing health motivation may be more efficient than promotional materials at the point of purchase (12) .…”
Section: Discussionmentioning
confidence: 99%
“…using purchase data) among this population [20][21][22][23], with some studies indicating that FOP labels may improve the nutritional quality of consumers' choices [22,23], and others reporting limited or null effects [20,21]. Evidence suggests that nutritional labels may be more effective when supported by measures to promote awareness, understanding and use of such labels [24,25], specifically when considering health-related outcomes [26]. Additionally, some studies have included highly educated participants [11,27], limiting the representativeness of results among lower income and education groups, which are the most representative of the Latin-American populations and generally the most nutritionally at-risk [28].…”
Section: Abstract: Nutritional Labeling Latin-america Shopping Timementioning
confidence: 95%
“…It is used on packaging in Norway, Sweden, Denmark and Iceland (Finland using the essentially equivalent Heart Symbol) to guide consumers to the healthiest choices within each food group according to recommendations for food composition. The symbol has been tested in different groups, showing a positive effect on the health perception of food and behaviour, at least in the short term [82,83]. A similar type of symbol used to guide the population towards more environmentally sustainable choices could be a useful tool of transformation.…”
Section: Towards a Healthy And Environmentally Sustainable Nordic mentioning
confidence: 99%